Historical and philosophical perspectives on the study of developmental bias. Issue 1 (29th July 2019) - Brigandt, Ingo
Abstract: Throughout the recent history of research at the intersection of evolution and development, notions such as developmental constraint, evolutionary novelty, and evolvability have been prominent, but the term "developmental bias" has scarcely been used. And one may even doubt whether a unique and principled definition of bias is possible. I argue that the concept of developmental bias can still play a vital scientific role by means of setting an explanatory agenda that motivates investigation and guides the formulation of integrative explanatory frameworks. Less crucial is a definition that would classify patterns of phenotypic variation and unify variational patterns involving different traits and taxa as all being "bias." Instead, what we should want is a concept that generates intellectual identity across various researchers, and that unites the diverse fields and approaches relevant to the study of developmental bias, from paleontology to behavioral biology. I point to some advantages of conducting research specifically under the label of "developmental bias, " compared with employing other, more common terms such as "evolvability." Abstract : Development introduces biases to phenotypic variation (as this figure from Oster and Albert 1982 illustrates). More specifically, the concept of developmental bias sets an explanatory agenda and coordinates research across diverse fields and approaches. Research Highlights: It may not be possible to arrive at a definition of developmental bias that classifies patterns of phenotypic variation involving different traits and taxa as all exhibiting "bias." But such a classificatory definition is not needed. The concept of developmental bias can play a vital role by setting an explanatory agenda that motivates research, provides intellectual identity across diverse fields and approaches investigating developmental bias, and coordinates the formation of integrative explanatory frameworks. Although there are other, more widely used notions pertaining to the generation of phenotypic variation, such as "evolvability, " there are reasons for conducting research specifically under the label of "developmental bias."